Gynecologic Surgeons' Perspectives on Risk Factors and Prophylaxis of Trocar Site Hernias: A National Survey [22Q]. (May 2018) - Wells, Ali; Germanos, George; Salemi, Jason; Mikhail, Emad
Abstract : INTRODUCTION: Although trocar site hernias (TSH) occur in only 1.5-1.8% of all laparoscopic procedures, TSHs can represent serious postoperative complications. The purpose of this study was to survey gynecologic surgeons who are active members of the Society of Laparoendoscopic Surgeons (SLS) in order to elicit their experiences with TSHs, including fascial closure preferences. METHODS: After reviewing the clinical and epidemiological literature to compile relevant questions, an anonymous survey was designed using Qualtrics web-based survey software. The survey link was sent to all members of SLS via email. Descriptive analyses included frequencies, percentages, and chi-square tests or Fisher's exact tests for measures of association. RESULTS: Respondents included 242 gynecologic surgeons, 54.2 % of whom reported at least one patient developing a TSH within the past 10 years. The likelihood of having ≥1 patient with TSH increased with higher monthly surgical volume; 39.5% for low-volume surgeons (⩽10 procedures/month) compared to 71.4% of high-volume surgeons (≥20 procedures/month) (p<0.01). Current use of fascial closure devices was more common among surgeons in an academic practice (60.3%) compared to those in private practice (39.6%, p <0.01). Among all respondents, 87.6%, 16.1%, and 2.5% close 10-12mm, 8mm, and 5mm ports, respectively, without differences according to surgical volume or practice setting. Approximately 6% reported closing more than one port size. CONCLUSION: Increased surgical volume is directly proportional to TSH development. Port size remains one of the main risk factors for TSH development, with most respondents closing only 10-12 mm ports irrespective of surgical volume or practice setting.